Get off your acid : 7 steps in 7 days to lose weight, fight inflammation and reclaim your health and energy - Gioffre, Daryl (Da Capo, 2018)
"Let's talk about the four-letter word that's secretly destroying your health: ACID. An acidic lifestyle--consuming foods such as sugar, grains, dairy, excess animal proteins, processed food, artificial sweeteners, along with lack of exercise and proper hydration, and stress--causes inflammation. And inflammation is the culprit behind many of our current ailments, from weight gain to chronic disease. But there's good news: health visionary Dr. Daryl Gioffre shares his revolutionary plan to rid your diet of highly acidic foods, alkalize your body and balance your pH. With the Get Off Your Acid plan, you'll: gain more energy, strengthen your immune system, diminish pain and reflux, improve digestion, focus, and sleep, lose excess weight and bloating, naturally. With alkaline recipes for easy, delicious snacks and meals, Get Off Your Acid is a powerful guide to transform your health and energy--in seven days"--Page [4] of cover.